Uncovering cargo clients and accessory factors of AP-1 and AP-4 through vesicle proteomics - Ziqing Peng; Jingran Fan; Yang Liu; Qinyu Jia; Junkun An; Jianying Wang; Yan Huang; Zhong-Ping Yao; Yusong Guo (Proceedings of the National Academy of Sciences, 2025)
The trans -Golgi network (TGN) is a crucial sorting station in the secretory pathway, where adaptor protein (AP) complexes ensure selective cargo packaging into transport vesicles. However, the complete repertoire of cargoes and regulators associated with individual AP complexes remains poorly defined. Intriguingly, AP-4-mediated TGN export operates independently of clathrin, suggesting the involvement of uncharacterized accessory factors in vesicle biogenesis. To address these gaps, we developed an in vitro vesicle formation assay using wild-type HeLa cells or cells deficient in AP1γ1 or AP4ε, reconstituting their roles in packaging their known clients, Vangl2 and ATG9A, respectively. Coupling this assay with label-free quantitative mass spectrometry, we mapped distinct cargo profiles for AP-1 (which buds from the TGN and ARF1-positive endosomes) and AP-4, identifying the 45 kDa calcium-binding protein (CAB45) as an AP-1-dependent cargo and the Type-1 angiotensin II receptor-associated protein (ATRAP) as an AP-4-dependent cargo. Additionally, we uncovered PRRC1 and WDR44 as cytosolic regulators essential for AP-4-mediated TGN export. Our study advances the mechanistic understanding of AP-1 and AP-4 in secretory trafficking and provides a robust strategy to systematically identify cargo clients and accessory factors for specific adaptor complexes.